The Impact of Rubella Virus Infection on a Secondary Inflammatory Response in Polarized Human Macrophages - Schilling, Erik; Grahnert, Anja; Pfeiffer, Lukas; Koehl, Ulrike; Claus, Claudia; Hauschildt, Sunna (Frontiers in Immunology, 2021)
Macrophages (MΦ) are known to exhibit distinct responses to viral and bacterial infection, but how they react when exposed to the pathogens in succession is less well understood. Accordingly, we determined the effect of a rubella virus (RV)-induced infection followed by an LPS-induced challenge on cytokine production, signal transduction and metabolic pathways in human GM (M1-like)- and M (M2-like)-MΦ. We found that infection of both subsets with RV resulted in a low TNF-α and a high interferon (IFN, type I and type III) release whereby M-MΦ produced far more IFNs than GM-MΦ. Thus, TNF-α production in contrast to IFN production is not a dominant feature of RV infection in these cells. Upon addition of LPS to RV-infected MΦ compared to the addition of LPS to the uninfected cells the TNF-α response only slightly increased, whereas the IFN-response of both subtypes was greatly enhanced. The subset specific cytokine expression pattern remained unchanged under these assay conditions. The priming effect of RV was also observed when replacing RV by IFN-β one putative priming stimulus induced by RV. Small amounts of IFN-β were sufficient for phosphorylation of Stat1 and to induce IFN-production in response to LPS. Analysis of signal transduction pathways activated by successive exposure of MΦ to RV and LPS revealed an increased phosphorylation of NFκB (M-MΦ), but different to uninfected MΦ a reduced phosphorylation of ERK1/2 (both subtypes). Furthermore, metabolic pathways were affected; the LPS-induced increase in glycolysis was dampened in both subtypes after RV infection. In conclusion, we show that RV infection and exogenously added IFN-β can prime MΦ to produce high amounts of IFNs in response to LPS and that changes in glycolysis and signal transduction are associated with the priming effect. These findings will help to understand to what extent MΦ defense to viral infection is modulated by a following exposure to a bacterial infection.